(untitled) (Politeja, 2023)
“INHERITING” HERITAGE: REMOVAL OF SOVIET MONUMENTS IN THE BALTIC STATES The aim of this article is an analysis of the process of removing the Soviet monuments including the objects commemorating the Red Army and those glorifying the Soviet regime, which were created during the occupation of the Baltic states by the USSR. After the spontaneous process of destroying the monuments and their removal in the 1990s, many of them remained in public spaces of the sovereign states. In recent years, due to Russia’s occupation of Crimea (2014) and Russia’s full-scale invasion of Ukraine (2022), the governments of Lithuania, Latvia and Estonia have taken active steps to dismantle monuments that are a symbol of Russian imperialism and falsification of history. The author draws attention to the process of heritage management, in which certain meanings are accepted and reinforced, while others are marginalised and rejected. Gregory Ashworth’s heritage paradigm will be used to analyse the research topic, according to which heritage is a process of selective acceptance or rejection of elements of the past in response to the current social, political and economic needs.